Essays on finance and decision theory - Goularte, Thiago Cyfer (2023)
This dissertation comprises two articles, both addressing the issue of decision-making in situations involving risk and uncertainty. The first article addresses the Reach-for-Yield effect, that is, the increase in risk-taking by economic agents in low-interest-rate scenarios. Such situations are interpreted as scenarios with low risk-free rates, causing economic agents to pursue higher risks to maintain their return levels. Most importantly, we contribute to the literature not only by identifying this effect in the Brazilian fund market but also by empirically investigating which of the proposed theories to explain this effect are plausible from an empirical standpoint. The second article, titled Salience Theory with Imprecise Information, proposes properties for probability weighting functions that can be used in conjunction with established risk decision theories (such as the Prominence Theory of Bordalo et al., 2012). This approach aims to incorporate stylized facts derived from the extensive growth of the literature on decision-making under ambiguity over the past two decades. Hence, our proposal seeks not only to accommodate but also to predict behaviors in line with recent developments in empirical and experimental literature